Systematic identification of trans eQTLs as putative drivers of known disease associations - Westra, Harm-Jan; Peters, Marjolein J; Esko, Tõnu; Yaghootkar, Hanieh; Schurmann, Claudia; Kettunen, Johannes; Christiansen, Mark W; Fairfax, Benjamin P; Schramm, Katharina; Powell, Joseph E; Zhernakova, Alexandra; Zhernakova, Daria V; et al. (Nature genetics, 2013)
Lude Franke and colleagues report the results of a large expression QTL study performed on peripheral blood samples from 5,311 individuals. They identify trans -eQTL effects for 103 independent loci that were previously associated with complex traits at genome-wide significance, suggesting that this approach can provide insights into the downstream effects of many trait-associated variants. Identifying the downstream effects of disease-associated SNPs is challenging. To help overcome this problem, we performed expression quantitative trait locus (eQTL) meta-analysis in non-transformed peripheral blood samples from 5,311 individuals with replication in 2,775 individuals. We identified and replicated trans eQTLs for 233 SNPs (reflecting 103 independent loci) that were previously associated with complex traits at genome-wide significance. Some of these SNPs affect multiple genes in trans that are known to be altered in individuals with disease: rs4917014, previously associated with systemic lupus erythematosus (SLE) 1 , altered gene expression of C1QB and five type I interferon response genes, both hallmarks of SLE 2 , 3 , 4 . DeepSAGE RNA sequencing showed that rs4917014 strongly alters the 3′ UTR levels of IKZF1 in cis , and chromatin immunoprecipitation and sequencing analysis of the trans -regulated genes implicated IKZF1 as the causal gene. Variants associated with cholesterol metabolism and type 1 diabetes showed similar phenomena, indicating that large-scale eQTL mapping provides insight into the downstream effects of many trait-associated variants.